Consumer acceptance of genetically modified foods [ - Evenson, Robert E. [ (Robert Eugene)] , 1934- (CABI, 2004)
In recent years there have been increasing concerns about the potential health risks of genetically modified foods. Consumer perceptions vary between countries, but are probably most pronounced in Europe and least in North America. These have had a profund and controversial effect on the development of markets for GM products. This book presents a compilation of studies of consumer acceptance of GM foods. These studies utilized different methods and evidence including: price and expenditure data; experimental methods; "willingness to pay"; consumer attitudes; and economic consequences.